Service oriented model driven architecture for dynamic workflow changes - Pudhota, Leo; Chang, Elizabeth (INSTICC Press, 2005)
Collaborative workflow management systems in logistic companies require strong information systems and computer support. These IT integration requirements have expanded considerably with the advent of e-business; utilizing web services for B2B (Business to Business) and P2P (Partner to Partner) e-commerce. This paper proposes service oriented model driven architecture for dynamic workflow changes and strategy for implementation of these changes by isolation of services and business processes where by existing workflow systems can easily incorporate and integrate the changes following a step by step process replacement synchronization in workflow. This paper will also describe conceptual framework for prototype implementation resulting in dynamic collaborative workflow management.